Assessment Of Quality-Of-Life Improvement In Severe Haemophilia-A With Inhibitor Patients Receiving Emicizumab Prophylaxis – Hospital Based Prospective Observational Study - Original Research Article (The Review of Diabetic Studies, 2025)
To assess Quality of Life Improvement following Emicizumab prophylaxis in severeHaemophilia- A patientsTo evaluate the impact on ABR and functional independence in hemophilia A patients. To assess the quality-of-life improvement in severe hemophilia patients on Emicizumab prophylaxis for the period of 6 months